Consent for Brain Tissue Donation after Intracerebral Haemorrhage: A Community-Based Study. - Neshika Samarasekera; Christine Lerpiniere; Arthur F Fonville; Andrew J Farrall; Joanna M Wardlaw; Philip M White; Antonia Torgersen; James W Ironside; Colin Smith; Rustam Al-Shahi Salman; Lothian Audit of the Treatment of Cerebral Haemorrhage (LATCH) collaborators (PLoS ONE)
Background Spontaneous intracerebral haemorrhage is a devastating form of stroke and its incidence increases with age. Obtaining brain tissue following intracerebral haemorrhage helps to understand its cause. Given declining autopsy rates worldwide, the feasibility of establishing an autopsy-based collection and its generalisability are uncertain. Methods We used multiple overlapping sources of case ascertainment to identify every adult diagnosed with intracerebral haemorrhage between 1st June 2010-31st May 2012, whilst resident in the Lothian region of Scotland. We sought consent from patients with intracerebral haemorrhage (or their nearest relative if the patient lacked mental capacity) to conduct a research autopsy. Results Of 295 adults with acute intracerebral haemorrhage, 110 (37%) could not be approached to consider donation. Of 185 adults/relatives approached, 91 (49%) consented to research autopsy. There were no differences in baseline demographic variables or markers of intracerebral haemorrhage severity between consenters and non-consenters. Adults who died and became donors (n = 46) differed from the rest of the cohort (n = 249) by being older (median age 80, IQR 76-86 vs. 75, IQR 65-83, p = 0.002) and having larger haemorrhages (median volume 23 ml, IQR 13-50 vs. 13 ml, IQR 4-40; p = 0.002). Conclusions Nearly half of those approached consent to brain tissue donation after acute intracerebral haemorrhage. The characteristics of adults who gave consent were comparable to those in an entire community, although those who donate early are older and have larger haemorrhage volumes.